Caracterização espectral da cultura do feijão dessecada e qualidade tecnológica dos grãos armazenados - Ganascini, Diandra (2019)
An alternative to the bean harvest at the appropriate time (physiological maturation) is the use of desiccants; however, depending on the way it is applied, type, time and mode of action, it can compromise the quality of the product, rendering it not usable. The storage of grains tends to cause the loss of quality and can lead to increasing of the hardness of the grains, cooking time, change of taste and color of the integument, and such loss can be augmented by the usage of disiccants. Therefore, the objective of this work was to evaluate the influence of the application of two different desiccant herbicides (diquat and ammonium glufosinate) on the bean crop by means of vegetation indexes, spectral curves and their derivatives after application, and through quality evaluation of grains submitted to different storage times. The experiment was carried out in two farms, in the municipality of Santa Tereza do Oeste, state of Paraná. The experimental design was completely randomized in subdivided plots, the plots were divided into five storage times (0, 2, 4, 6, and 8 months) and redivided into two different desiccants (diquat and ammonium glyphosinate) and control with five repetitions. In Article 1, the spectral characterization of the plots in the different treatments was performed, then the vegetation indices (IVs) and those derived from the spectral curve were calculated. The vegetation indices (IV), the IVP and IVM length ranges of the treatments with desiccant application presented ≤0.05 from the second day after application (DAD), being possible to identify visually in the wavelengths (705, 750, 860 and 1240 nm) in the spectral curves. The NDWI and mNDI IVs presented p≤0.05 in the first DAD. The use of desiccant causes degradation of chlorophyll, which can be observed in the first DAD in the region of the wavelengths (650 and 800 nm). By means of the red edge parameter and the first derivative it is possible to observe the stress generated in the plant, being more expressive with the application of diquat, since the magnitude of the peaks with the application of diquat becomes smaller with the passing of days. It has been observed that the bean is a human consumed legume, the application of desiccant interfered negatively in the quality of the grains, with increase in its cooking time (TC) and reduction of Hue (coloring angle). In addition, it was observed that the Hue presented a negative correlation (-0.52) with the water content of the plant and (-0.59) with TC. It is concluded that it is possible to differentiate the effects caused by the desiccants, showing that the ammonium-glufosinate presents less damage to the quality, presenting loss of water similar to the control. In the Article 2 the grain characterization was carried out, evaluating the following grain variables: productivity, water content, grain size, color parameters, cooking time, texture, and electrical conductivity. The results for productivity and water content did not present statistical differences, and the control obtained higher productivity. It was observed that the prolonged storage time leads to a decrease in grain size. As for color, it was observed that storage causes browning of the grains and with the application of desiccants this effect is more pronounced. The cooking time and texture of the dried grains is higher than the control and the diquat presented the greatest time and resistance, and it is possible to observe that these values increase progressively along with storage time. It is concluded that the application of pre-harvest desiccants influences the technological quality of the grains, being this effect more accentuated with the grain storage